Petrophysical properties of crystalline rocks - Harvey, P. K. (Geological Society special publication ;, 2005)
Boreholes are commonly drilled into crystalline rocks to evaluate their suitability for various applications such as waste disposal (including nuclear waste), geothermal energy, hydrology, sequestration of greenhouse gases and for fault analysis. Crystalline rocks include igneous, metamorphic and even some sedimentary rocks. This volume covers the following aspects of the petrophysical properties of crystalline rocks: fracturing and deformation, oceanic basement studies, permeability and hydrology, and laboratory based studies.